Transition from Socialism - Arrow, Kenneth J. (Estudios Económicos de El Colegio de México, 1991)
This paper discusses the changes that socialist countries, especially in Eastern Europe, are currently undergoing. It also comments on the decline all over the world of the institution of the nation-state, and, particularly, a decline in its importance in the economy.